PENGEMBANGAN MODEL INDEX MULTIDIMENSI UNTUK PREDIKSI PROGNOSIS EKSASERBASI PADA PASIEN PPOK - Nuni Apriani; Anggriyana Tri Widiyanti; Gissan Rafli Ikbari; Riki Hermawan (UIMA Press, 2024)
Background: Acute exacerbations are a major cause of poor outcomes in patients with Chronic Obstructive Pulmonary Disease (COPD). However, attention to early recognition of acute exacerbation symptoms has been limited to FEV1 (Forced Expiratory Volume in 1 second). COPD is a complex disease that involves many dimensions, so early symptom recognition requires a more comprehensive multidimensional assessment. This study is a retrospective cohort study to develop a multidimensional index model in assessing the prognosis of exacerbations in COPD patients. Objectives: This study aims to find a comprehensive index model in the early assessment of exacerbations to reduce mortality and morbidity in COPD patients. Methods: This study is a retrospective cohort study by conducting non-interventional observations. A total of 28 COPD patients based on GOLD (Global Initiative for Chronic Obstructive Lung Disease) criteria were included as respondents. Results: The Cox Regression survival analysis for the quartiles showed a significant effect of this multidimensional index on predict exacerbation prognosis. Conclusion: The BODEX + sPO2 provided an adequate match between predicted and observed exacerbation prognosis in COPD.